2022
DOI: 10.1186/s10194-022-01457-1
|View full text |Cite
|
Sign up to set email alerts
|

Total tenderness score and pressure pain thresholds in persistent post-traumatic headache attributed to mild traumatic brain injury

Abstract: Objective To investigate whether persistent post-traumatic headache attributed to mild traumatic brain injury (TBI) is associated with more pronounced pericranial tenderness and lower pressure pain thresholds (PPTs) in the head and neck region, compared with healthy controls. Methods Patients with persistent post-traumatic headache (n = 100) and age- and gender-matched healthy controls (n = 100) were included between July 2018 and June 2019. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Beyond the scope of the ARMR questionnaires, peri-cranial tenderness and pressure pain thresholds may also reflect altered nociceptive thresholds in patients who develop persistent PTH following mTBI. 34 While clear PTH-specific patterns of somatosensory dysfunction have yet to emerge, 35 our findings support the overall theme that hypersensitivity is present across multiple sensory modalities in PTH and contributes to post-TBI symptom burden.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Beyond the scope of the ARMR questionnaires, peri-cranial tenderness and pressure pain thresholds may also reflect altered nociceptive thresholds in patients who develop persistent PTH following mTBI. 34 While clear PTH-specific patterns of somatosensory dysfunction have yet to emerge, 35 our findings support the overall theme that hypersensitivity is present across multiple sensory modalities in PTH and contributes to post-TBI symptom burden.…”
Section: Discussionsupporting
confidence: 66%
“…This prior work has led to the proposed notion that allodynia may be more “PTH‐specific” than other features, when clinically differentiating post‐concussive headache from other nontraumatic headaches, though evidence is mixed 33 and the characteristics of the ARMR dataset prohibited direct examination of this factor (discussed further below). Beyond the scope of the ARMR questionnaires, peri‐cranial tenderness and pressure pain thresholds may also reflect altered nociceptive thresholds in patients who develop persistent PTH following mTBI 34 . While clear PTH‐specific patterns of somatosensory dysfunction have yet to emerge, 35 our findings support the overall theme that hypersensitivity is present across multiple sensory modalities in PTH and contributes to post‐TBI symptom burden.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Studies have demonstrated evidence for thermal and mechanical sensitization among those with posttraumatic headache 29 . For example, there is greater pericranial tenderness and reduced pressure pain thresholds in the head and neck regions among those with persistent posttraumatic headache 30 . This sensitized state can be exacerbated by exposing individuals to bright light, which may be evidence for atypical multisensory integration in those with posttraumatic headache 19 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Decreased pain thresholds in post-traumatic headache had been shown in a few studies [ 20 , 21 ], but a demonstration of this had not been done with a large cohort. A recent study compared 100 patients with persistent post-traumatic headache after a mild TBI with 100 healthy age- and gender-matched controls [ 22 ]. The tenderness of the pericranial muscles and pressure pain thresholds at m. temporalis and m. trapezius (upper and middle part) were examined in both groups.…”
Section: Headache Phenotyping Using Quantitative Sensory Testingmentioning
confidence: 99%